Training of Volunteers in Psychological First Aid and Coping Strategies - Becerra, Luciana (2021)
Objective. To analyze the effectiveness of volunteer and professional personnel who assist in emergencies (Volunteer Firefighters, Civil Defense, Red Cross) in a Psychological First Aid training program and its relationship with indicators of empathy and coping strategies. Method. A quantitative, comparative, and co-relational study was carried out with a sample of 198 volunteers belonging to institutions that intervene in emergencies. A simulation program on responses to victims of catastrophes was used, Interactive System in Psychological First Aid and the Coping Strategies Inventory. Results. Volunteers, who state that handle better stressful situations, achieve a more effective performance in the simulation program. The assessment of the context as threatening or indifferent impaired the execution of the proposed PFA protocol using software.